Improvisation of non-conformance management in a small aerospace manufacturing industry - Zulkifli, Norzima; Thevendram, Kausalyah (Zibeline International Publishing, 2019)
This study is specifically concerned on the improvisation of non-conformance management process in a small aerospace manufacturing industry. Robust actions on root cause analysis and corrective actions (RCCA) is vital to achieve good yield and sustain the business. Hence, in the present study, the key objective is to identify the wastes in the non-conformance process flow and improvise the overall non-conformance management process. There were three specific objectives determined in order to achieve the main objective. Firstly, a model database was established to capture all the data and linked to populate graphs and charts for analysis purpose. Some of the significant QC tools were implemented as part of the enhancement process. The second objective is to improvise and integrate robust root cause analysis method using the 5-Why tool and Fishbone Diagram tool. Finally, the third objective is to improve the effectiveness of corrective action monitoring and verification of the process. The results from these improvisations were analysed in terms of the overall reject rate, repetition of defects, parts per million and finally the effectiveness of the corrective action. The improvements resulted in a reduction of scrap rate from 0.8% to 0.6% which eventually met the company’s objective. Significant changes were observed from the variations implemented that would benefit small scale companies in the future.